A Comparative Survey on Big Data Analytics using Hadoop - Jagwinder Singh, Er. Sandeep Kaur, Harmanjeet Singh (International Journal of Advanced Science and Technology, 2020)
With the origin of digital era and social media platforms, the enormous amount of data which isproduced rapidly at the constant rate is a big challenge. The data has started to cross all the boundsof the system, servers and the entire information centre. So with this large amount of data the big datawill came into existence. Consequently, big data is a probable research area that has competent tacticof providing valuable information. Moreover with this challenge, the new technologies have beendeveloped. The paper will focus on the technologies which are vital in handling the challenge of bigdata. The most noteworthy methodology in taking care of huge information is the Hadoop system, asthe paper will feature its parts of structure and furthermore the working procedure inside the system.